Answer:
[tex]a = \frac{7}{2}[/tex] and [tex]b = \frac{-69}{4}[/tex]
Step-by-step explanation:
Given
[tex]y = x^2 + 7x - 5[/tex]
Required:
Write as:
[tex]y = (x + a)^2 + b[/tex]
Determine the values of a and b
[tex]y = x^2 + 7x - 5[/tex]
[tex]y = (x + a)^2 + b[/tex]
Expand
[tex]y = x^2 + 2ax + a^2 + b[/tex]
So, we have:
[tex]y = x^2 + 2ax + a^2 + b[/tex]
[tex]y = x^2 + 7x - 5[/tex]
By comparison:
[tex]2ax = 7x[/tex]
[tex]a^2 + b = -5[/tex]
Solve for x in: [tex]2ax = 7x[/tex]
[tex]2a = 7[/tex]
Divide through by 2
[tex]a = \frac{7}{2}[/tex]
Substitute [tex]a = \frac{7}{2}[/tex] in [tex]a^2 + b = -5[/tex]
[tex](\frac{7}{2})^2 + b = -5[/tex]
[tex]\frac{49}{4}+ b = -5[/tex]
Make b the subject
[tex]b = -5 -\frac{49}{4}[/tex]
[tex]b = \frac{-20-49}{4}[/tex]
[tex]b = \frac{-69}{4}[/tex]